ANALISIS KEBUTUHAN PENGEMBANGAN VIDEO PEMBELAJARAN PADA MATA KULIAH TEORI DAN PRAKTIK BATU BETON - Fildzah Ghassani Athaya (ADISAM PUBLISHER, 2024)
The development of technology in this digital era has a positive impact, one of which is in the field of education. Students in this digital era have easier access to teaching materials other than books, one of which is video. The development of learning videos has become one of the effective methods in supporting the learning process of students in various courses, including Theory and Practice of Concrete Stone courses. This study aims to analyze the need for developing learning videos in the Theory and Practice of Concrete Stone courses. The needs analysis method was carried out using a questionnaire survey distributed to students of the State University of Jakarta who had completed the Theory and Practice of Concrete Stone courses. Based on the results of the analysis that has been carried out, 80% of students state that the learning media used today does not help students understand the material presented. 88.6% stated that the learning media used today does not attract student attention. 100% agreed to the development of new learning media in the Theory and Practice of Concrete Stone course. 100% stated that learning media in the form of videos can make it easier for students to understand the material